2020
DOI: 10.1017/s0025315420000132
|View full text |Cite
|
Sign up to set email alerts
|

Rough-toothed dolphins (Cetartiodactyla: Delphinidae) habitat use in coastal urban waters of the South-western Atlantic

Abstract: Rough-toothed dolphins (Steno bredanensis) are regularly present in continental shelf areas of the South-western Atlantic. However, there is little information on the natural history and ecology of these delphinids. This study evaluated the occurrence, habitat use and individual movements of the species in coastal waters off Rio de Janeiro, south-eastern Brazil. Data were obtained from boat surveys between August 2011 and May 2018, during which rough-toothed dolphins were sighted in 21 distinct events, predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The inner portions of GB could constitute important feeding grounds for S. bredanensis , as recently observed by Lodi and Maricato (2020). Off‐effort sightings suggested that this species could be using the area more than expected.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The inner portions of GB could constitute important feeding grounds for S. bredanensis , as recently observed by Lodi and Maricato (2020). Off‐effort sightings suggested that this species could be using the area more than expected.…”
Section: Introductionsupporting
confidence: 56%
“…In Brazil, one study has investigated the population structure of S. bredanensis and documented the presence of a southeastern population (Silva et al, 2015). However, mark-recapture efforts with the sole aim of investigating nearshore occurrences are still scarce, and only a few records have been documented, which have suggested that individual site fidelity is linked to aspects of habitat use (Lodi & Maricato, 2020). Furthermore, dedicated efforts to investigate population abundance are lacking in the SWAO.…”
Section: Introductionmentioning
confidence: 99%
“…Certain overlaps observed between rough-toothed dolphins and Guiana dolphins raise concerns about the long-term viability of rough-toothed dolphin populations inhabiting coastal areas, such as site fidelity to polluted areas and in foraging grounds . Rough-toothed dolphins from SE Brazil are observed year-round in the coast of RJ state using enclosed bays, as the GB, which are relevant foraging areas for this apex predator, but also increase the risk of exposure to pollutants. Therefore, assessing the damage that such pollutants may cause to coastal populations of rough-toothed dolphins becomes imperative.…”
Section: Resultsmentioning
confidence: 99%
“…These areas are also important for several cetacean species. The Guanabara Bay, for example, located in the metropolitan area of Rio de Janeiro state, in SE Brazil, is one of the most degraded environments on the Brazilian coast, highly eutrophic, and yet an important resource supplier to rough-toothed dolphins. , Most samples from this site were collected inside or around the area of the Guanabara Bay.…”
Section: Methodsmentioning
confidence: 99%
“…The rough-toothed dolphin inhabits tropical, subtropical and warm-temperate waters in all three major oceans, mostly between 40°N and 35°S. This species usually occurs in oceanic waters deeper than 1,000 m, but also in shallower waters (until 30 m or less) (West et al 2011;Jefferson 2018;Lodi & Maricato 2020). This species lives in relatively small groups, mostly ranging from 10-20 individuals, although larger groups up to 50 or more individuals and mixed groups in association with other species have been documented (Jefferson 2018).…”
Section: Introductionmentioning
confidence: 99%